2011
DOI: 10.1093/europace/eur198
|View full text |Cite
|
Sign up to set email alerts
|

Induction and aggravation of atrioventricular valve regurgitation in the course of chronic right ventricular apical pacing

Abstract: Considering the haemodynamic effects at mid-term follow-up, left ventricular dysfunction is rare in patients with RV apical pacing and normal baseline left ventricular function. Right ventricular apical pacing is associated with a significant increase in the prevalence and severity of TR and MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 18 publications
3
24
0
2
Order By: Relevance
“…Several other studies have also assessed TR before and after device implantation using echocardiography. 4,5,8,11,31 However, only one of those studies 8 evaluated the TV after lead implantation using 3D imaging. Previous studies using 2D imaging were unable to define mechanisms associated with increased TR post device lead placement and were therefore unable to separate TR secondary to lead interference from other causes.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have also assessed TR before and after device implantation using echocardiography. 4,5,8,11,31 However, only one of those studies 8 evaluated the TV after lead implantation using 3D imaging. Previous studies using 2D imaging were unable to define mechanisms associated with increased TR post device lead placement and were therefore unable to separate TR secondary to lead interference from other causes.…”
Section: Discussionmentioning
confidence: 99%
“…Post-MitraClip hemodynamics confirmed dramatic improvement in left atrial pressures throughout both paced and native rhythms ( Figure 5, Table 1). Transthoracic echocardiography on postoperative day 1 showed a mild decrease in left ventricular size and modest drop in left ventricular ejection fraction from 60-65% to 45-50% but with sustained mild residual MR. clinical scenarios ranging from acute severe MR immediately following pacemaker implantation to slow progression of MR in the setting of chronic right ventricular apical pacing [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who require pacemakers or internal cardiac defibrillators commonly have a permanent lead placed across the tricuspid valve (TV) into the right ventricle. However, multiple studies have shown development of TV dysfunction due to leads traversing the TV with up to 24% of patients developing worsening of TR by 1 grade and up to 5.3 % developing severe tricuspid regurgitation (TR) . Mechanisms of this lead‐induced TR include physical damage to the TV apparatus as well as reaction of tissue to the lead …”
Section: Introductionmentioning
confidence: 99%